The role of Ikeda Daisaku in the activities of the Buddhist neo-religious society Soka Gakkai - R. M. Seitov; E. E. Voytishek (Японские исследования)
Soka Gakkai is one of the largest neo-religious organizations in Japan and is based on the ideology of Nichirenism. It was created in 1930 but became widespread and gained popularity after the Second World War. Today, it has millions of members both in Japan and abroad, it also has educational institutions from kindergartens to universities, its own media outlets, a representative office at the UN, and significant influence on the country’s domestic politics. In its modern form, the organization owes much to the efforts of Ikeda Daisaku, the third president and spiritual leader, as well as the founder of the political party Komeito. He had a colossal influence on the development of Soka Gakkai, creating a powerful bureaucratic structure in it, and brought its activities to the international arena. Gradually, D. Ikeda moved away from formal management of affairs, but, as the honorary president of the organization, he continued to direct the activities and ideology of the society. At the same time, many processes in the organization turned out to be focused on exploiting the image of D. Ikeda, who occupied a central place in all religious and secular affairs. In the official publications of Soka Gakkai, D. Ikeda appears as a writer, pacifist, intellectual, and educator. Numerous diplomatic, educational, and peacekeeping activities, the opening of schools, museums, and universities, and the writing and publication of a multi-volume collection of works are attributed to his personal initiative. The rise of D. Ikeda can be explained by the orientation of Nichirenism toward the continuity of teachings through charismatic leadership. After his death in 2023, there was no other authoritative leader in Soka Gakkai, and there was a threat of destabilization and disintegration of the organization and the loss of its political influence. At the same time, the refusal to transfer charismatic leadership to a successor, apparently, was a conscious decision made by the bureaucratic apparatus of the organization. The article examines the evolution of the personality and image of Ikeda Daisaku and his role in the activities of the Soka Gakkai at the present stage.